Flagelo: mask and denunciation The Indigenist Theater of Jorge Icaza - Landázuri, Andrés (2021)
This article seeks to account for the indigenist project of Ecuadorian writer Jorge Icaza (Quito, 1906-1978) by exploring a minor and relatively little known work of the author: the play Flagelo. Presumably written in 1932 and published for the first time in 1936, Flagelo may well be taken as the gateway to Icaza’s indigenism, understood as a specific delimitation within “Ecuadorian social realism”. An attempt is made to provide a reading that exposes the procedures and conflicts that give rise to the work in question, while allowing to establish its ideologized and political character, without undermining its artistic workmanship and its particular successes as a scenic product.